Convergence Rate Analysis of the Proximal Difference of the Convex Algorithm. (4th January 2021) - Wang, Xueyong; Zhang, Ying; Chen, Haibin; Kou, Xipeng
Abstract : In this paper, we study the convergence rate of the proximal difference of the convex algorithm for the problem with a strong convex function and two convex functions. By making full use of the special structure of the difference of convex decomposition, we prove that the convergence rate of the proximal difference of the convex algorithm is linear, which is measured by the objective function value.